Framing and communicating climate change: the effects of distance and outcome frame manipulations - Spence, Alexa; Pidgeon, Nick (Elsevier, 2010)
Communications regarding climate change are increasingly being utilised in order to encourage sustainable behaviour and the way that these are framed can significantly alter the impact that they have on the recipient. This experimental study seeks to investigate how transferable existing research findings on framing from health and behavioural research are to the climate change case. The study (N = 161) examined how framing the same information about climate change in terms of gain or loss outcomes or in terms of local or distant impacts can affect perceptions. Text on potential climate change impacts was adapted from the 2007 Intergovernmental Panel on Climate Change report, alongside maps and images of potential flooding impacts. Participants then completed measures of various relevant socio-cognitive factors and questions assessing their responses to the information that they had received. Results indicated that, ceteris paribus, gain frames were superior to loss frames in increasing positive attitudes towards climate change mitigation, and also increased the perceived severity of climate change impacts. However, third variable analyses demonstrated that the superiority of the gain frame was partially suppressed by lower fear responses and poorer information recall within gain framed information. In addition, framing climate change impacts as distant (whilst keeping information presented the same) resulted in climate change impacts being perceived as more severe, while attitudes towards climate change mitigation were more positive when participants were asked to consider social rather than personal aspects of climate change. Implications for designing communications about climate change are outlined.